Next-generation sequencing in chronic lymphocytic leukemia: recent findings and new horizons - Rodríguez-Vicente, Ana E; Bikos, Vasilis; Hernández-Sánchez, María; Malcikova, Jitka; Hernández-Rivas, Jesús-María; Pospisilova, Sarka (Oncotarget, 2017)
The rapid progress in next-generation sequencing technologies has significantly contributed to our knowledge of the genetic events associated with the development, progression and treatment resistance of chronic lymphocytic leukemia patients. Together with the discovery of new driver mutations, next-generation sequencing has revealed an immense degree of both intra- and inter-tumor heterogeneity and enabled us to describe marked clonal evolution. Advances in immunogenetics may be implemented to detect minimal residual disease more sensitively and to track clonal B cell populations, their dynamics and molecular characteristics. The interpretation of these aspects is indispensable to thoroughly examine the genetic background of chronic lymphocytic leukemia. We review and discuss the recent results provided by the different next-generation sequencing techniques used in studying the chronic lymphocytic leukemia genome, as well as future perspectives in the methodologies and applications.
Keywords: next-generation sequencing; chronic lymphocytic leukemia; immunogenetics; clonal evolution; CLL prognosis